Nanofluid thermo-bio-convection in a horizontal porous wavy-walled annulus: Interaction of phototactic microorganisms and nanoparticles distribution - Belabid, Jabrane; Öztop, Hakan Fehmi (Pergamon-Elsevier Science Ltd, 2023)
Transport phenomena related to thermo-bioconvection have recently emerged as an intriguing area of study because of their multi-physical applications such as bio-energy systems, food industries, solar collectors, pollutant dispersion in aquifers, biological wastes processing, chemical catalytic converters, geothermal energy usage, petroleum oil reservoirs, enhanced oil recovery, thermal energy storage, chemical processing equipment, fuel cell technology, medical application, microfluidic devices, and others. In this context, it is highly challenging to design and regulate a system with multi-physical transport in a complex geometry. The goal of the current study is to analyze the thermo-bioconvective heat transfer induced by a gradient of temperature and a motile of phototactic microorganisms with the presence of two types of nanoparticles inside a wavy-walled horizontal cylindrical porous annulus. The originality of this investigation is analyzing the influence of microorganisms, waviness parameters and hybrid nanofluid on thermo-convective instabilities. The effects of the wall waviness parameters, bioconvection Rayleigh number (Rab), thermal Rayleigh number (RaT), nanoparticles volume fraction & phi; and Lewis number (Le) on the flow structure, temperature, and isoconcentrations of microorganisms are investigated and explained in detail. The key findings showed that the Lewis number impacts the onset of thermo-convection and bioconvection and convection phenomena begins rapidly for small values of Lewis number. The nanoparticles enhance the heat transfer in case of thermo-bioconvective flow in a horizontal porous cylindrical system. The average Nusselt number Nu decreases as the wall waviness parameters, amplitude & lambda;, and undulation number & eta; increase. It was also shown that thermo-convective instabilities may develop depending on thermal Rayleigh number, bioconvection Rayleigh number, nanoparticles volume fraction and wall waviness parameters.
Keywords: Bioconvection; Wavy enclosures; Phototactic micoorrganisms; Heat transfer; Hybrid nanofluid; Porous annulus